2017
DOI: 10.4209/aaqr.2017.03.0114
|View full text |Cite
|
Sign up to set email alerts
|

Influences of Waste Cooking Oil-Based Biodiesel Blends on PAH and PCDD/F Emissions from Diesel Engines in Durability Testing Cycle

Abstract: In this study, the 60,000-km durability tests were performed on two diesel engines (EURO IV and EURO II) by using B10 (10% waste cooking oil + 90% diesel) and B8 (8% waste cooking oil + 92% diesel), respectively, to determine the impacts on the emissions of polycyclic aromatic hydrocarbons (PAHs) and polychlorinated dibenzo-p-dioxins and dibenzofurans (PCCD/Fs). The above emissions were measured per 20,000-km testing intervals. The highest total PAH mass concentrations were 38.2 and 25.6 µg Nm -3 before durabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 47 publications
(60 reference statements)
0
4
0
Order By: Relevance
“…The lower HC emission ensures that the combustion is perfect with the fuel's good atomization [71,72]. Redfern et al [73] performed a 60,000 km durability test on a EURO II and a EURO IV diesel engine using B10 and B8 blends. They found that total polycyclic in the EURO II engine aromatic hydrocarbons emissions was less when biodiesel was used.…”
Section: Emission Characteristicsmentioning
confidence: 99%
“…The lower HC emission ensures that the combustion is perfect with the fuel's good atomization [71,72]. Redfern et al [73] performed a 60,000 km durability test on a EURO II and a EURO IV diesel engine using B10 and B8 blends. They found that total polycyclic in the EURO II engine aromatic hydrocarbons emissions was less when biodiesel was used.…”
Section: Emission Characteristicsmentioning
confidence: 99%
“…Increased consumption of liquid fossil fuels and rising fuel prices with constant demands to reduce environmental pollution from the exhaust gases of internal combustion engines are leading to an intensified search for alternative solutions, especially to replace diesel fuel, which plays a significant role as fuel for diesel engines in transport vehicles and in a wide range of mobile machinery used in construction, agriculture and many other industrial activities. Diesel engines were reported as one major mobile emission sources of pollutants, including carbon monoxide (CO), total hydrocarbons (HC), nitrogen oxides (NOx), and particulate matter (PM) [1]. Together with the development of high conversion efficiency diesel engines, cost-effective after treatment technologies and advanced clean combustion concepts, using cleaner alternative fuels is one of the focuses of pollutant reduction techniques [2].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers are concerned by mobile source air pollution, which causes environmental problems and is associated with adverse health effects. Compared with gasoline engines, diesel engines yield more emissions of pollutants, including soot, black smoke, nitrogen oxides, trace metals (Liati et al, 2015) and harmful components (e.g., polycyclic aromatic hydrocarbons (PAHs) and polychlorinated dibenzo-p-dioxins and dibenzofurans (PCDD/Fs)) (Cheruiyot et al, 2016;Redfern et al, 2017;Tsai et al, 2018). Diesel PM has a diameter smaller than 1 µm, and thus can be easily inhaled into the respiratory system (Baldauf et al, 2016;Gao and Tian, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Biodiesel is recognized to be one of the ways to successfully reduce diesel engine pollutant emissions (Wang et al, 2016;Lin et al, 2017;Redfern et al, 2017). Biodiesel is environmentally friendly, but has slightly higher fuel consumption (Mwangi et al, 2015;Lin et al, 2017) and levels of trace metals on the particles in the exhausts than standard diesel fuel under the same operating conditions (Shukla et al, 2017).…”
Section: Introductionmentioning
confidence: 99%